Absorbed water in the cork structure. A study by thermally stimulated currents, dielectric relaxation spectroscopy, isothermal depolarization experiments and differential scanning calorimetry - Dionísio, M. S. C.; Correia, N. T. (Journal of materials …, 1995)
This paper reports on a modification of the dielectric properties of cork which occurs as a consequence of heating above 60 ~ C or evacuation for several days. This phenomenon was observed using different experimental techniques (thermally stimulated currents, dielectric relaxation spectroscopy, isothermal depolarization experiments and differential scanning calorimetry), and the corresponding kinetics were analysed. It was observed that the original properties of cork were recovered if the sample was exposed to room air for several weeks. It is suggested that the reported modification of the dielectric properties arises from desorption, induced by heating or evacuation, of water molecules absorbed in the cork structure.
Keywords: Cellular structure (voyant); Cork; dielectric loss; dielectric relaxation; TSDC; water desorption